The Role of The National Unity and Political Agency in Increasing Political Participation in The 2024 Election Era - Prakasa, Septian Erianto; Zafira, Nadia Lutfi; Heryanto, Yanto (Jurnal Polisci, 2025)
Background. The role of the National Unity and Politics Agency (Kesbangpol) in increasing public political participation during the 2024 Election. Aims. This research aims to analyze the role of Kesbangpol in political participation through the theory of political participation by Sidney Verba and Norman H. Nie as an analysis deep.   Methods. The research in Majalengka Regency uses a qualitative method with observational data sources, interviews, and documentation studies to further carry out validity tests through data triangulation. Result. The study's results show that Kesbangpol plays a strategic role as a facilitator through political education programs, inclusive discussion spaces, and the use of digital media, thereby increasing access to political information. Although Majalengka Regency won the title of the third-highest city/Regency in West Java with a community political participation rate of 76.91 percent, this figure is not optimal because it falls below the West Java KPU target of 86%. Conclusion. The researcher incorporated culture as a complement to Sidney's theory, which originated from Western countries, thereby introducing novelty to the research. Implementation. Culture is an additional element to support increasing community participation in Indonesia, especially in Majalengka Regency.